(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Background: Mental health treatment in children and adolescents involves both pharmacological and non-pharmacological methods. Pharmacotherapy is considered when symptoms are severe or non-pharmacological treatments are ineffective. Due to limited data on psychotropic prescribing patterns in children and adolescents in Nepal, this study aims to: (a) examine prescribing patterns in a tertiary care outpatient setting, (b) identify different psychotropics used and (c) determine the proportion of patients receiving these medications. Methods: This study retrospectively examines the records of children and adolescents at the outpatient department of Child and Adolescent Psychiatry Unit (CAP), Kanti Children’s Hospital (KCH), Nepal. Approval for the study was granted by KCH’s Institutional Review Board (Reference no: 125). The analysis focused on data extracted from hospital records of outpatients at CAP Unit, KCH from 1st January 2024 to 31st December 2024 encompassing one year. Results: Among 6,855 children and adolescents, 1,345 (19.62%) received prescriptions for psychotropic medications. Adolescents were the most common recipients of psychotropics (50.70%, n = 682), followed by school-aged children (43.12%, n = 580), and preschool children (6.17%, n = 83). The most commonly used psychotropic was sertraline (38.73%, n = 521), followed by risperidone (16.87%, n = 227), clonazepam (15.24%, n = 205), and atomoxetine (11.59%, n = 156). Among the different categories of psychotropics, selective serotonin reuptake inhibitors(SSRis) were the most frequently prescribed (57.24%, n = 770), followed by antipsychotics (24.16%, n = 325), benzodiazepines (21.24%, n = 286), and medications for Attention Deficit Hyperactivity Disorder (16.13%, n = 217). Monotherapy was observed in 77.39% (n = 1,041) of children and adolescents, making it more common than polypharmacy, which was observed in 22.60% (n = 304). Conclusion: The study highlights key patterns in psychotropic prescribing among children and adolescents at a tertiary center in Nepal, with SSRIs and risperidone being the most frequently used. Adolescents were the primary recipients, and monotherapy was more common than combination treatments.